Determinants of the intention to create a spin-off in Spanish universities. (2017) - Miranda, Francisco Javier; Chamorro, Antonio; Rubio, Sergio
With the growth in the popularity of the concept of an entrepreneurial university, over recent decades the commitment from European universities to commercialising research findings through the creation of spin-offs has also grown. In this way, academics become potential entrepreneurs or, as they are called in the business literature, intrapreneurs. Taking into account that the theories regarding planned behaviour consider intention as the main antecedent of behaviour, the aim of this paper is to test the influence that certain variables - demographic, psychological and those relating to the environment - have on the intention of academics in Spanish universities to create a spin-off. After conducting a survey of 1, 178 academics from all fields of knowledge, the results show that the variables influencing this intention to be an entrepreneur are entrepreneurial personality, gender, academic experience and the entrepreneurial abilities of the individual, as well as the perceived utility of being an entrepreneur, the assessment of the economic environment and the productivity of their research group in terms of patents and articles published. Identifying the profile of the academics with the greatest entrepreneurial intention can help to guide university policy in matters of transferring knowledge and promoting spin-offs as an alternative way of commercialising research findings.